Analysis of the Influence of Salary, Social Security, and Company Facilities on Employee Welfare of PT NPK Kebun Bahilang - Natalia Sianipar, Christin; Parulian Sirait, Niko (International Conference on Health Science, Green Economics, Educational Review and Technology, 2020)
This study aims to determine how the influence of salary, sosial security, and company facilities on employee welfare. This study used a sample of 90 respondents who is an employee of Tebing Tinggi. The results of hypothesis testing using multiple linear regression analysis with three independent variables and one dependent variable indicate that: salary variable (X1) has a positive and significant effect on employee welfare (Y) PT NPK Kebun Bahilang Tebing Tinggi, sosial security (X2), has a positive and significant effect Significant to employee welfare (Y) PT NPK Kebun Bahilang Tebing Tinggi, company facilities (X3) has a positive and significant effect on employee welfare (Y) PT NPK Kebun Bahilang Tebing Tinggi. Salary variable (X1) , social security (X2), and company facilities (X3) have a joint effect on the walfare variable.